Design & fabrication of 2-in-1 gardening tools / Muhammad Ilhan Harith Mohd Faizul - Mohd Faizul, Muhammad Ilhan Harith (2023)
Pesticide sprayer has played an important role in human history as an equipment that is used to apply pesticides on agricultural crops. Farmers frequently spray pesticides with a backpack pesticide sprayer, which they must carry around with them at all times. They have to physically pump the pesticide and continually refilling it because the tank capacity is limited and it only has one nozzle, they must travel around a lot to cover the entire farm. Back discomfort and extreme tiredness are common side effects of long-term usage, especially among large-scale plantation producers. As a result, the farmers’ health will suffer, reducing their productivity. Therefore, the objective of this project is to design and fabricate pesticide wheel pump sprayer. Observational data is gathered by watching farmers using their pesticide sprayer. This expected result for this project will help farmers to save their time and help them to avoid any injuries